Ahlu al-Assunnah wa Al-Jama'ah Studies in Religious Character Building in Islamic Schools - Nur Khofifah, Sinta; Qomaruddin, Qomaruddin; Fadlillah, Nilna; Ahmad, Nur Fatih; Mahfudloh, Ririn Inayatul (Journal of Education and Religious Studies, 2025)
This study aims to evaluate the effectiveness of the Aswaja Study Program in shaping the religious character of class XI students at SMK Islamic Qon Gresik. With a qualitative approach and case study method, data were collected through observation, interviews, and documentation. Data analysis followed four stages with source triangulation for validity. The results showed significant improvement in four aspects of students' religious character: awareness of worship (prayer consistency, ritual participation), moral improvement (courtesy, respect for differences), development of tolerance (inclusive interaction, dialogue between groups), and transformation of religious understanding (spiritual internalization, social care). Success is supported by institutional support, quality of teachers, discussions, case studies, field trips, student enthusiasm, and relevance of materials. Obstacles include differences in basic understanding, inconsistent attendance, limited method innovation, and lecture saturation. Implementation strategies include interactive routine studies, exemplary teachers, integration of values in the curriculum, and collaboration with extracurricular activities. Globally, this model indicates that the internalization of moderate religious values (tawassuth, tasamuh, tawazun, i'tidal) has the potential to be an effective strategy in strengthening adolescents' religious character, preventing radicalism, and enriching moderate religious literacy. This model is worth adapting in vocational and general education institutions in Muslim countries as well as global communities facing the challenges of intolerance and extremism. This research examines the impact of the Aswaja religious studies program, which matches your interest in education and religious programs